Chapter «Buona strada, Papà!» - Turan, Emin (Libere carte, 2023)
In David Sassoli, intelligence and cognitive awareness are placed at the service of primordial ethical values: in the passionate defence of knowledge, freedom and commitment to the common good. His deep and strong love for life expands to the way he fraternises, speaks or acts, with a relentless lucidity and moral demand. It is this attitude, this way of exercising citizenship and doing politics, that is recognisably unique and fascinating in him. An independent person who, standing outside the dominant logic and power, attracted others by his authenticity, his example, by the inner voice of a truth, which emerges.